Kangaroo mother care diminishes pain from heel lance in very preterm neonates: A crossover trial - McNaughton Kathryn; Bell Linda; Goulet Celine; Campbell-Yeo Marsha; Filion Francoise; Johnston C Celeste; Byron Jasmine; Aita Marilyn; Finley G Allen; Walker Claire-Dominique (BMC, 2008)
Abstract Background Skin-to-skin contact, or kangaroo mother care (KMC) has been shown to be efficacious in diminishing pain response to heel lance in full term and moderately preterm neonates. The purpose of this study was to determine if KMC would also be efficacious in very preterm neonates. Methods Preterm neonates (n = 61) between 28 0/7 and 31 6/7 weeks gestational age in three Level III NICU's in Canada comprised the sample. A single-blind randomized crossover design was employed. In the experimental condition, the infant was held in KMC for 15 minutes prior to and throughout heel lance procedure. In the control condition, the infant was in prone position swaddled in a blanket in the incubator. The primary outcome was the Premature Infant Pain Profile (PIPP), which is comprised of three facial actions, maximum heart rate, minimum oxygen saturation levels from baseline in 30-second blocks from heel lance. The secondary outcome was time to recover, defined as heart rate return to baseline. Continuous video, heart rate and oxygen saturation monitoring were recorded with event markers during the procedure and were subsequently analyzed. Repeated measures analysis-of-variance was employed to generate results. Results PIPP scores at 90 seconds post lance were significantly lower in the KMC condition (8.871 (95%CI 7.852-9.889) versus 10.677 (95%CI 9.563-11.792) p < .001) and non-significant mean differences ranging from 1.2 to1.8. favoring KMC condition at 30, 60 and 120 seconds. Time to recovery was significantly shorter, by a minute(123 seconds (95%CI 103-142) versus 193 seconds (95%CI 158-227). Facial actions were highly significantly lower across all points in time reaching a two-fold difference by 120 seconds post-lance and heart rate was significantly lower across the first 90 seconds in the KMC condition. Conclusion Very preterm neonates appear to have endogenous mechanisms elicited through skin-to-skin maternal contact that decrease pain response, but not as powerfully as in older preterm neonates. The shorter recovery time in KMC is clinically important in helping maintain homeostasis. Trial Registration (Current Controlled Trials) ISRCTN63551708